BMD101: Mandarin Language I / Academy of Language Studies - UiTM, Academy of Language Studies (2021)
The Elementary Mandarin Language course is intended for students who have no background in Mandarin or any character-based language. This is the first of a three-level Mandarin Language programme designed specifically for UiTM Diploma students. The students will be taught appropriate elementary level vocabulary and grammar. The course will emphasize greatly on developing participants oral communication skills in situational contexts through class activities such as role plays, simulations and other relevant oral tasks. Students are expected to take part in all language activities conducted in class to ensure success in attaining the elementary level proficiency. In this course, students will be introduced to the Hanyu Pinyin system. In addition, Chinese culture will also be introduced in this course.